Valorization of a Residue of the Kombucha Beverage Industry Through the Production of Dehydrated Water Dispersible Cellulose Nanocrystals - Alonso, Laura Giselle (2025)
In this study, cellulose nanocrystals (CNCs) were successfully isolated through the acid hydrolysis of freeze-dried and oven-dried bacterial nanocellulose (BNC) recovered from the floating pellicle generated during Kombucha tea production. The influence of the BNC drying method and its concentration on the yield and main characteristics of the CNCs obtained were studied. Additionally, selected CNC suspensions at various pH levels were subjected to freeze-drying and oven-drying, followed by an assessment of their dispersibility in water after undergoing different mechanical treatments. Results demonstrate the potential of utilizing byproducts from the expanding Kombucha industry as an alternative cellulose source for CNC production. Furthermore, the drying method applied to the BNC and its initial concentration in the hydrolysis medium were found to significantly impact the properties of the resulting CNCs, which exhibited diverse size distributions and Z-potential values. Finally, the redispersion studies highlighted the beneficial effect of drying CNCs from neutral and alkaline dispersions, as well as the requirement of ultrasound treatments to achieve the proper dispersion of dehydrated CNC powders.